Transcriptomic responses to drought stress in Polygonatum kingianum tuber - Huali Qian (BMC, 2021)
Abstract Background Polygonatum kingianum Coll. et Hemsl. is an important plant in Traditional Chinese Medicine. The extracts from its tubers are rich in polysaccharides and other metabolites such as saponins. It is a well-known concept that growing medicinal plants in semi-arid (or drought stress) increases their natural compounds concentrations. This study was conducted to explore the morpho-physiological responses of P. kingianum plants and transcriptomic signatures of P. kingianum tubers exposed to mild, moderate, and severe drought and rewatering. Results The stress effects on the morpho-physiological parameters were dependent on the intensity of the drought stress. The leaf area, relative water content, chlorophyll content, and shoot fresh weight decreased whereas electrolyte leakage increased with increase in drought stress intensity. A total of 53,081 unigenes were obtained; 59% of which were annotated. We observed that 1352 and 350 core genes were differentially expressed in drought and rewatering, respectively. Drought stress driven differentially expressed genes (DEGs) were enriched in phenylpropanoid biosynthesis, flavonoid biosynthesis, starch and sucrose metabolism, and stilbenoid diarylheptanoid and gingerol biosynthesis, and carotenoid biosynthesis pathways. Pathways such as plant-pathogen interaction and galactose metabolism were differentially regulated between severe drought and rewatering. Drought reduced the expression of lignin, gingerol, and flavonoid biosynthesis related genes and rewatering recovered the tubers from stress by increasing the expression of the genes. Increased expression of carotenoid biosynthesis pathway related genes under drought suggested their important role in stress endurance. An increase in starch and sucrose biosynthesis was evident from transcriptomic changes under drought stress. Rewatering recovered the drought affected tubers as evident from the contrasting expression profiles of genes related to these pathways. P. kingianum tuber experiences an increased biosynthesis of sucrose, starch, and carotenoid under drought stress. Drought decreases the flavonoids, phenylpropanoids, gingerol, and lignin biosynthesis. These changes can be reversed by rewatering the P. kingianum plants. Conclusions These results provide a transcriptome resource for P. kingianum and expands the knowledge on the effect of drought and rewatering on important pathways. This study also provides a large number of candidate genes that could be manipulated for drought stress tolerance and managing the polysaccharide and secondary metabolites’ contents in P. kingianum.